Promoting an Artist as an Integral Part of Diplomatic Networking: Chiappino Vitelli and Federico Zuccari at the Court of Queen Elizabeth I - Mavilla, Francesca (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2020)
In the field of study on relations between Italy and Flanders in the second half of the sixteenth century, the military leader Gian Luigi, better known as Chiappino, Vitelli (1520–75) deserves special attention. Trusted man of Cosimo I de’ Medici and maestro di campo generale of the Spanish armies in Flanders since 1567, he was among the protagonists of the first ten years of the Dutch Revolt. Based on the identification of new archival documents, this essay aims both to broaden the sphere of investigation and deepen the understanding of the role of Chiappino in cultural exchanges between Florence, the Habsburg’s and Elizabeth I’s courts. At the same time, it is aimed to draw attention to the political and cultural dynamics in which Chiappino Vitelli’s action towards the English Queen is embedded. From the documents, it clearly emerges how Vitelli took advantage of his role to earn the favour of the sovereign and, in addition to his loyalty, he did not hesitate to offer her the most varied of gifts, such as animals, weapons and artists, such as the painter Federico Zuccari, who reached Flanders in 1574. Zuccari’s sending to the English court should be interpreted as an attempt by the military leader to gain the favour of Elizabeth I when the support of the courts of Florence and Madrid seemed to be lacking, especially after the death of Cosimo de’ Medici and the replacement of the Duke of Alba as governor of Flanders.